2013
DOI: 10.1007/s00114-013-1094-6
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopes document resource partitioning and effects of forest disturbance on sympatric cheirogaleid lemurs

Abstract: The future of Madagascar's forests and their resident lemurs is precarious. Determining how species respond to forest fragmentation is essential for management efforts. We use stable isotope biogeochemistry to investigate how disturbance affects resource partitioning between two genera of cheirogaleid lemurs (Cheirogaleus and Microcebus) from three humid forest sites: continuous and fragmented forest at Tsinjoarivo, and selectively logged forest at Ranomafana. We test three hypotheses: (H1) cheirogaleids are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 91 publications
2
27
0
Order By: Relevance
“…and Cheirogaleus sp. : Crowley, Blanco, Arrigo‐Nelson, & Irwin, ). However, the ability to incorporate novel foods likely depends on habitat, severity of disturbance, and the species' degree of specialty.…”
Section: Introductionmentioning
confidence: 99%
“…and Cheirogaleus sp. : Crowley, Blanco, Arrigo‐Nelson, & Irwin, ). However, the ability to incorporate novel foods likely depends on habitat, severity of disturbance, and the species' degree of specialty.…”
Section: Introductionmentioning
confidence: 99%
“…Across all TA, most sources ( n = 63) covered species threatened with extinction. Four DD species were also included in research (DD lemur species: furry‐eared dwarf lemur, Cheirogaleus crossleyi : Crowley, Blanco, Arrigo‐Nelson, & Irwin, 2013), and 62 species across the total sample (13.5%) were not listed by the IUCN. Two studies considered insects, each exploring how the ecosystem services the insects provided were impacted by fragmentation (pollination: Bodin, Tengö, Norman, Lundberg, & Elmqvist, 2006; seed dispersal: Dausmann, Glos, Linsenmair, & Ganzhorn, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…For “Other” studies, Crowley et al (2013) used stable isotope analysis to examine resource partitioning in response to fragmentation between mouse and dwarf lemurs (Goodman's mouse lemur, Microcebus lehilahytsara ; furry‐eared dwarf lemur, C. crossleyi ; Sibree's dwarf lemur, C. sibreei ), finding these cheirogaleids to modify behavioral strategies to consume similar resources across sites, despite the impact of fragmentation on resource availability. Two other studies also examined nutrition and resource access.…”
Section: Resultsmentioning
confidence: 99%
“…Loudon et al () found nitrogen enrichment in ring‐tailed lemurs ( Lemur catta ) in suboptimal health. Crowley et al () found slightly higher δ 15 N (∼0.5‰) in Cheirogaleus crossleyi in the fragmented forests of Tsinjoarivo, but were unable to ascertain if the increase in δ 15 N was due to increased insect consumption or nutritional stress. Ben‐David, McColl, Boonstra, and Karels (), however, found no effect between food restriction and isotope composition, although it was noted that physiological effects (i.e., stable nitrogen composition) may have been obscured by diet selection.…”
Section: Discussionmentioning
confidence: 97%
“…The establishment of the Institute for the Conservation of Tropical Environments by Wright led to collaborations and exchanges among scientists resulting in over 800 publications from 1987 to 2016. Of the nearly 100 publications that focus on the effects of logging or habitat modification in the rainforests of eastern Madagascar, the majority address compositional or functional change at the species or population level (e.g., Crowley et al, ; Crowley, Blanco, Arrigo‐Nelson, & Irwin, ; Gerber, Arrigo‐Nelson, Karpanty, Kotschwar, & Wright, ; Herrera, Wright, Lauterbur, Ratovonjanahary, & Taylor, ; Irwin et al, ; Pochron, Tucker, & Wright, ; Wright, ). Research on the effects of logging on composition or function at the community level comprises ∼20% of the total (e.g., Benstead, Douglas, & Pringle, ; Bixby, Benstead, Douglas, & Pringle, ; Brown & Gurevitch, ; Bublitz et al, ; Rainio & Niemelä, ; Razafindratsima, Jones, & Dunham, ; Wright et al, ), while research on the effects of logging on structural/compositional and functional attributes of the genetic component of biodiversity accounts for ∼10% of the total (e.g., Baden et al, ; Tomiuk et al, ; Yoder et al, ).…”
Section: Introductionmentioning
confidence: 99%